The chronology of third molar root mineralization in south Indian population. (January 2014) - Maled, Venkatesh; Manjunatha, B; Patil, Karthikeya; Balaraj, BM
The aim of present study was to determine the chronology of third molar root mineralization and to establish south Indian reference data. Therefore, a cross-sectional study was undertaken by evaluating 192 intraoral periapical radiographs in order to assess the root mineralization status of the mandibular third molar of south Indian individuals (101 males and 91 females) between the age of 13 and 25. The evaluation was carried out using the seven-stage developmental scheme of Kullman et al. (1992). The range, mean age, standard deviation, Student t test and percentile distributions are presented for each stage of mineralization. Statistically significant differences between males and females were not found. All individuals from this study with mature third molar roots were at least 18 years of age. For medicolegal purposes, the likelihood of whether a south Indian individual is older than 18 years or not was determined.